The Efficiency Calculation for Combination Continuously Variable Speed Transmission - 薛隆泉; 苏志霄; 郗向儒; 崔亚辉; 杨华成 (Jixie chuandong)
In this paper the driving efficiency of combination continuously variable speed transmission has been analyzed by the node power method of three axis system.Then the efficiency calculation formula of this drive is given.The calculation result by this method is more close to the measured result then transmission ratio method.It can provide the basis for the further design of the combination continuously variable speed transmission.